The Evolution of FinTech and its Effects on Financial Decision Making: A Systematic Literature Review - Mahmudi, Bambang (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The development of FinTech technology has changed the financial landscape, having a significant impact on individual and corporate financial decision-making. Through a systematic literature review, this research investigates the evolution of FinTech and its effects on financial management behavior, product preferences, investment decisions, and consumer confidence. FinTech has improved accessibility, product innovation, data analysis, competition in the market, and security, while also raising challenges such as data security issues and the risk of bias in decision making. With a deeper understanding of this relationship, steps can be taken to maximize the benefits of FinTech while minimizing the risks.